Basically, all you have to do is substitue the terms given at the top.
x = -3
y = 6
z = -4
The first one will be set up like this:
(-3) + 6 + (-1) = 2
The second one will be set up like this:
-15 + (- -3) + 6 = -6
The third one will be set up like this:
3(-3) - 2(6) + (-4) = -25
The fourth one will be set up like this:
2(-4) - 3 (6) + 4(-3) = -38
The fifth one will be set up like this:
3 ( -3) + 2 (6) + (-4) = -1
The sixth will be set up like this:
(-3)(-4)
---------- = -1
-2 (6)
The seventh will be set up like this:
2 (6) (-4) - 3 (-3) = -39
Hope this helps! Have a good day/night! c: